Ummi Method Implementation: Tahfidzul Qur'an at SMP IT Luqmanul Hakim Yogyakarta - Hapizi, M; Risky, Abu; Widodo, Hendro (Al Hikmah: Journal of Education, 2024)
Memorizing the holy book Al-Quran is something difficult and difficult, not only is there a lot of verses but the Al-Quran is completely Arabic so it is difficult. This assumption is actually not entirely true. Because, there are several activities to make memorizing easier, such as murojaah or repeating memorization well and consistently. The Tahfidz learning method at SMPIT LHI refers to the UMMI method. The Ummi method is a systematic system in learning the Koran which consists of three main components, namely, practical books on the Ummi method, quality management of the Ummi method and professional and certified teachers. Therefore, this research seeks to explore and analyze the application of the ummi method in learning Tahfidzul Quran at SMPIT LHI, The research uses a qualitative approach with a case study type. Researchers are the main instrument that plays a role. In conclusion, the implementation of the tahfidz curriculum at SMPIT Banguntapan includes good planning, can be implemented, continuous assessment and supervision, The novelty in this research is that it explains Ummi's method systematically and responsibly. is expected to be an asset and good implementation of tahfidz activities at SMPIT LHI Banguntapan.